Formulation, Evaluation, and Comparison of Herbal Shampoo with Commercially Available Shampoos - Telrandhe, Mr. Umesh B. (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: A shampoo is essentially a detergent solution with appropriate ingredients for additional advantages such as improved hair conditioning, lubrication, and medicine. There are many different types of shampoos on the market today; including synthetic, herbal, medicated, and non-medicated varieties, but herbal shampoo is becoming more and more popular among customers due to their perception that natural goods are risk-free and without adverse effects. Aim: The aim of the present study is to formulate herbal shampoo, and evaluate and compare its physicochemical properties with the commercially available shampoos. Materials and Methods: The herbal shampoo was formulated by adding the extracts of Calendula officinalis, Lawsonia inermis, Citrus limonum, Citrus ulgaric, and Santolina trifoliatus in different proportions to a 10% aqueous gelatin solution. Small amount of methylparaben was added as a preservative and pH was adjusted with citric acid. Several quality control tests such as physical appearance/visual inspection, pH, solid contents, foam test, viscosity test, dirt dispersion test, surface tension, wetting test, and conditioning performance tests were performed to determine the physicochemical properties of formulated herbal shampoo and commercial shampoos. The formulated herbal shampoo and commercial shampoo were also evaluated for conditioning performance by blind test on twenty volunteers. Results and Discussion: The results revealed that our formulated herbal shampoo was transparent. The results showed good cleansing and detergency, normal pH, low surface tension, small bubble size, good viscosity, and foam stability after 5 min. The formulated shampoo and commercial shampoos also showed comparable results for % solid contents. The score of the conditioning performance of the tress washed with herbal shampoo was found to be 3.2 out of 4, while the score of the commercial shampoo was 3.1 and 3.3, respectively. Conclusion: Our results revealed that the formulated herbal shampoo has excellent conditioning performance, at par with commercially available shampoo. However, further research and development is required to improve its quality and safety.